THE SURVIVABILITY OF SMALL MICRO ENTERPRISE (SME) IN INDRAGIRI HULU DURING THE EPIDEMIC (JURNAL MANAJEMEN DAN BISNIS, 2021)
The spread of Corona Virus in along 2020 is unpredictable and uncontrolled. According to this condition, a lot of Big Company weakened and got involved in to a worst situation and even collapse. And of course, Small Micro Enterprise (SME) will be or had been bothered by the impact. Indonesian Government has made various efforts to avoid the effects of the COVID-19 epidemic on SME. There are a lot of ways and approaches implemented to overcome it. The objectives of the study is to find win-win solution for SME to keep survive during the COVID-19 epidemic. The population of the study is the Indragiri Hulu SME Entrepreneurs. The Category of five years are selected to be the sample which is limited to 10 successful survival entrepreneurs that represents the descriptive category. Moreover, the data analysis technique used in this study was data analysis with a data reduction model that was obtained from data collection and data display. The results of this study show six strategies based on push and pull factors theories, as social psychology theory which develop the survivalist entrepreneurship in Indragiri Hulu. The strategy also needs to pay attention on opportunity, added value, necessity, overcome and avoiding dissatisfaction of the previous way. Furthermore, it is also suggested that an entrepreneur of SME players needs to play strategy in order to establish and survive the business during the epidemic, because the epidemic is not the end of everything.